2006
DOI: 10.1002/adma.200601215
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Growth of BiFeO3–CoFe2O4 Nanostructures

Abstract: Multifunctional materials have attracted increasing interest in recent years because of their potential applications in novel technological devices. [1][2][3][4][5][6][7][8][9][10][11] [12] The ferroelectric and magnetic properties as well as the degree of the coupling are critically dependent on the morphology of the nanostructures, including domain patterns and shapes as well as the interfaces. In order to pursue the enhanced multifunctionality, significant effort has been made on understanding the growth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
285
3
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(330 citation statements)
references
References 28 publications
26
285
3
5
Order By: Relevance
“…The room temperature single-phase multiferroic, BiFeO 3 (BFO), has attracted a lot of recent research interest due to the coexistence of robust ferroelectricity (P) and antiferromagnetism (L) [13][14][15][16][17][29][30][31][32][33][34][35][36] and a weak canted magnetic moment (M C ). In bulk BFO, the weak moment results from the canting of the magnetic sublattices due to the Dzyaloshinskii-Moriya interaction 14 as predicted by the density functional theory 14 and confirmed experimentally 30,36 .…”
mentioning
confidence: 99%
“…The room temperature single-phase multiferroic, BiFeO 3 (BFO), has attracted a lot of recent research interest due to the coexistence of robust ferroelectricity (P) and antiferromagnetism (L) [13][14][15][16][17][29][30][31][32][33][34][35][36] and a weak canted magnetic moment (M C ). In bulk BFO, the weak moment results from the canting of the magnetic sublattices due to the Dzyaloshinskii-Moriya interaction 14 as predicted by the density functional theory 14 and confirmed experimentally 30,36 .…”
mentioning
confidence: 99%
“…The 0 G Mn ferrite film has a pyramid-like domain structure which seems to be faceted along (111) planes. Previously, it was reported that spinel oxide nanostructures of CoCr 2 O 4 on MgO (001) [26] or CoFe 2 O 4 on SrTiO 3 (001) [27] substrates tend to grow into pyramid-like grains along {111} planes to minimize the surface energy. It has to be noted that the surface energy in spinels is strongly anisotropic, with the {111} planes having the minimal surface energy [27].…”
Section: Resultsmentioning
confidence: 99%
“…If the period is determined by thermal diffusion, then it should be inversely proportional to the growth rate. 28,29 Figure 4b shows the change of the in-plane and out-of-plane lattice parameters with the deposition rate. This figure shows the in-plane lattice parameter as constant within error, irrespective of the deposition rate.…”
Section: Resultsmentioning
confidence: 99%